2018
DOI: 10.1002/pssa.201800068
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Method with Low Hydrothermal Temperature to Synthesize TiO2 as Controlled Release Drug Delivery

Abstract: Titania is obtained by taking titanium oxysulfate sulfuric acid complex hydrate as Ti source with a simple, energy saving process. The effect of hydrothermal time and temperature on morphology is investigated. The particle size and morphology are analyzed by X-Ray diffraction (XRD), field emission scanning electron microscopy (FESEM), energy dispersive X-ray spectroscopy (EDS), and Raman spectroscopy. Additionally, the effect of tetracycline/TiO 2 ratio on drug loading capacity and encapsulation rate are studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…LDHs consist of hydroxide host layers and interlayer anions, with the general formula of [M 2+ 1− x M 3+ x (OH) 2 ](A n − ) x / n · m H 2 O (Gao & Yan, ; D. Liu, Lin, Tang, Deng, & Bi, ; Z. Liu, Lin, Zhao, et al, ; C. Liu, Qin, et al, ; W. Liu, Xu, et al, ; Shao et al, ; Tian et al, ; Q. Wang & O'Hare, ). Notably, LDHs nanosheets can be taken up by specific types of cancer cells via clathrin‐mediated endocytosis, thus leading to the resistance to endosomal effects with buffering properties (G. Choi et al, ).…”
Section: Layered Double Hydroxidesmentioning
confidence: 99%
See 4 more Smart Citations
“…LDHs consist of hydroxide host layers and interlayer anions, with the general formula of [M 2+ 1− x M 3+ x (OH) 2 ](A n − ) x / n · m H 2 O (Gao & Yan, ; D. Liu, Lin, Tang, Deng, & Bi, ; Z. Liu, Lin, Zhao, et al, ; C. Liu, Qin, et al, ; W. Liu, Xu, et al, ; Shao et al, ; Tian et al, ; Q. Wang & O'Hare, ). Notably, LDHs nanosheets can be taken up by specific types of cancer cells via clathrin‐mediated endocytosis, thus leading to the resistance to endosomal effects with buffering properties (G. Choi et al, ).…”
Section: Layered Double Hydroxidesmentioning
confidence: 99%
“…For example, g‐C 3 N 4 nanosheets have been developed as drug delivery response to pH for effective cancer therapy (S. Liu et al, ). In another recent study, it has been reported that g‐C 3 N 4 nanosheets exhibit high drug loading capacity towards DOX (D. Liu, Lin, Tang, et al, ; Z. Liu, Lin, Zhao, et al, ; C. Liu, Qin, et al, ; W. Liu, Xu, et al, ). Interestingly, because of the excellent fluorescence imaging ability of g‐C 3 N 4 nanosheets, the drug delivery process can be directly visualized for potential diagnostic purpose (Figure a).…”
Section: Other 2d Nanomaterials For Drug Deliverymentioning
confidence: 99%
See 3 more Smart Citations